Crop-to-wild geneflow: environmental risk assessment for the release of genetically modified sorghum in Kenya - Evans, Mutegi (University of the Free State, 2009)
The important socio-economic position enjoyed by sorghum has made it a target for genetic modification to enhance productivity and/or nutritional quality. However, there are growing environmental concerns that through geneflow, transgenes might escape from genetically modified (GM) sorghum to its sexually compatible wild and/or weedy relatives, with possible negative effects. Characterising the levels and dynamics of geneflow in the wild-weedy-domesticate complex of sorghum in traditional groecosystems of Africa, including Kenya, is of interest to biosafety regulators. This study used approaches based on population genetics theory to (i) characterise the genetic structure of the wild-weedy-domesticate complex of S. bicolor at a country scale in Kenya and (ii) to estimate the extent and direction of geneflow between cultivated and wild-weedy populations at a local scale in the country. The structure and dynamics of diversity was first estimated and compared at country scale by genotyping 329 cultivated and 110 wild sorghum individuals using 24 microsatellite markers. Subsequently, the magnitude and direction of geneflow between the two congeners was estimated at a local scale by analysing 483 individuals comprising of 15 wild-weedy and 12 cultivated sorghum populations using 10 microsatellite markers. Overall, cultivated sorghum harboured lower diversity than its wild counterpart. Levels of genetic diversity in cultivated and wild sorghum differed significantly among regions, with most of the diversity being partitioned more within than among the crop’s growing regions. There were generally low levels of differentiation within and between cultivated and wild sorghum at country scale, but the extent of crop-to-wild genetic proximity varied among sorghum growing regions. These findings may reflect important historical geneflow between cultivated sorghum and its progenitor, with the level of crop-to-wild genetic exchange varying among regions. At local scale, the extent of geneflow was approximately nine times higher from cultivated sorghum to its wild-weedy relatives than vice versa. Additionally, the extent of crop-to-wild geneflow varied significantly among farms. Overall, this study suggests that deployment of GM sorghum in Kenya’s agroecosystems will most likely lead to movement of transgenes into sympatric populations of its wild-weedy relatives.

Die belangrike sosio-ekonomiese posisie van sorghum het dit die ideale gewas vir genetiese modifikasie vir produktiwiteit en/of voedingskwaliteitsverbetering gemaak. Daar is egter groeiende kommer oor die omgewing, aangesien geenvloei transgene ontsnapping vanaf geneties gemodifiseerde (GM) sorghum na wilde en/of onkruid kruisingsversoenbare verwante kan veroorsaak, met moontlike negatiewe effekte. Die karakterising van die vlakke en dinamika van geenvloei in die wilde-onkruidagtigeverboude kompleks van sorghum in tradisionele agro-ekosisteme van Afrika, Kenia ingesluit, is van belang vir bioveilgheidsreguleerders. Hierdie studie het die benadering van populasiegenetikateorie gebruik om (i) die genetiese struktuur van die wildeonkruidagtige- verboude kompleks van S. bicolor binne die hele Kenia te karakteriseer en (ii) om die hoeveelheid en rigting van geenvloei tussen verboude en wilde-onkruidagtige populasies op ‘n plaaslike vlak binne die land te bepaal. Die struktuur en dinamika van diversiteit is eers bepaal en toe nasionaal vergelyk deur 329 verboude en 110 wilde sorghum individue met 24 mikrosatelliet merkers. Daarna is die hoeveelheid en rigting van geenvloei tussen die twee groepe op plaaslike skaal bepaal deur toetsing van 483 individue bestaande uit 15 wilde-onkruidagtige en 12 verboude sorghum populasies met 10 mikrosatelliet merkers te evalueer. In die geheel het verboude sorghum minder diversiteit as die wilde groep getoon. Vlakke van genetiese diversiteit in verboude en wilde sorghum het betekenisvol tussen streke verskil, met meer diversiteit binne as tussen streke. Daar was oor die algmeen lae vlakke van differensiasie binne en tussen verboude en wilde sorghum op nasionale vlak, maar die gewas-na-wilde genetiese afstand het tussen sorghum produksie areas gewissel. Hierdie bevindinge kan die belangrike historiese geenvloei binne verboude sorghum en die bron van afkoms reflekteer, met die vlak van gewas-na-wilde uitruiling wat verskil tussen streke. Op ‘n plaaslike vlak was die hoeveelheid geenvloei ongeveer nege keer hoër van verboude sorghum na die wildeonkruidagtige verwantes as andersom. Verder het die vlak van gewas-na-wilde geenvloei betekenisvol tussen plase verskil. In die geheel dui hierdie studie aan dat die vrystelling van GM sorghum in Kenia se agro-ekosisteem waarskynlik na die beweging van transgene na simpatriese populasies van die wilde-onkruidagtige verwantes sal lei.
Thesis (Ph.D. (Plant Breeding))--University of the Free State, 2009
Keywords: Autocorrelation; Diversity; Genetic structure; Introgression; Phylogeography; Sorghum bicolor; Spatial analysis; Wild-weedy-domesticate complex; Transgenic plants -- Risk assessment -- Kenya; Sorghum -- Breeding -- Kenya; Environmental risk assessment